MAVARIC - a comparison of automation-assisted and manual cervical screening: A randomised controlled trial - Kitchener, H; Blanks, R; Cubie, H; Desai, M; Dunn, G; Legood, R; Gray, A; Sadique, Z; Moss, S (2011)
Objectives: The principal objective was to compare automation-assisted reading of cervical cytology with manual reading using the histological end point of cervical intraepithelial neoplasia grade II (CIN2) or worse (CIN2+). Secondary objectives included (i) an assessment of the slide ranking facility of the Becton Dickinson (BD) FocalPoint™ Slide Profiler (Becton Dickinson, Franklin Lakes, NJ, USA), especially 'No Further Review', (ii) a comparison of the two approved automated systems, the ThinPrep® Imaging System (Hologic, Bedford, MA, USA) and the BD FocalPoint Guided Screener Imaging System, and (iii) automated versus manual in terms of productivity and cost-effectiveness. Design: A 1: 2 randomised allocation of slides to either manual reading or automationassisted paired with manual reading. Cytoscreeners were blinded to whether samples would be read only manually or manually paired with automated. Slide reading procedures followed real-life laboratory protocol to produce a final result and, for paired readings, the worse result determined the management. Costs per event were estimated and combined with productivity to produce a cost per slide, per woman and per CIN2+ and cervical intraepithelial neoplasia grade III (CIN3) or worse (CIN3+) lesion detected. Costeffectiveness was estimated using cost per CIN2+ detected. Lifetime cost-effectiveness in terms of life-years and quality-adjusted life-years was estimated using a mathematical model. Setting: Liquid-based cytology samples were obtained in primary care, and a small number of abnormal samples were obtained from local colposcopy clinics, from different women, in order to enrich the proportion of abnormals. All of the samples were read in a single large service laboratory. Liquid residues used for human papillomavirus (HPV) triage were tested (with Hybrid Capture 2, Qiagen, Crawley, UK) in a specialist virology laboratory in Edinburgh, UK. Histopathology was read by a specialist gynaecological pathology team blinded to HPV results and type of reading. Participants: Samples were obtained from women aged 25-64 years undergoing primary cervical screening in Greater Manchester, UK, with small proportions from women outside this age range and from women undergoing colposcopy. Interventions: The principal intervention was automation-assisted reading of cervical cytology slides which was paired with a manual reading of the same slide. Low-grade cytological abnormalities (borderline and mild dyskaryosis) were triaged with HPV testing to direct colposcopy referral. Women with high-grade cytology were referred for colposcopy and those with negative cytology were returned to recall. Main outcome measures: The principal outcome measure was the sensitivity of automation-assisted reading relative to manual for the detection of CIN2+. A secondary outcome measure was cost-effectiveness of each type of reading to detect CIN2+. The study was powered to detect a relative sensitivity difference equivalent to an absolute difference of 5%. Results: The principal finding was that automated reading was 8% less sensitive relative to manual, 6.3% in absolute terms. 'No further review' was very reliable and, if restricted to routine screening samples, < 1% of CIN2+ would have been missed. Automated and manual were very similar in terms of cost-effectiveness despite a 60%-80% increase in productivity for automation-assisted reading. Conclusions: The significantly reduced sensitivity of automated reading, combined with uncertainty over cost-effectiveness, suggests no justification at present to recommend its introduction. The reliability of 'no further review' warrants further consideration as a means of saving staff time. Trial registration: Current Controlled Trials ISRCTN66377374. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 15, No. 3. See the HTA programme website for further project information. © Queen's Printer and Controller of HMSO 2011. All rights reserved.